If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 18) + 2(x + 9) = x + -54 Reorder the terms: 3(18 + x) + 2(x + 9) = x + -54 (18 * 3 + x * 3) + 2(x + 9) = x + -54 (54 + 3x) + 2(x + 9) = x + -54 Reorder the terms: 54 + 3x + 2(9 + x) = x + -54 54 + 3x + (9 * 2 + x * 2) = x + -54 54 + 3x + (18 + 2x) = x + -54 Reorder the terms: 54 + 18 + 3x + 2x = x + -54 Combine like terms: 54 + 18 = 72 72 + 3x + 2x = x + -54 Combine like terms: 3x + 2x = 5x 72 + 5x = x + -54 Reorder the terms: 72 + 5x = -54 + x Solving 72 + 5x = -54 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 72 + 5x + -1x = -54 + x + -1x Combine like terms: 5x + -1x = 4x 72 + 4x = -54 + x + -1x Combine like terms: x + -1x = 0 72 + 4x = -54 + 0 72 + 4x = -54 Add '-72' to each side of the equation. 72 + -72 + 4x = -54 + -72 Combine like terms: 72 + -72 = 0 0 + 4x = -54 + -72 4x = -54 + -72 Combine like terms: -54 + -72 = -126 4x = -126 Divide each side by '4'. x = -31.5 Simplifying x = -31.5
| -13=x/5-7 | | 2p-60=5p | | 2a+5b=186 | | 3a+5=2a+7 | | -2-(4-3p)= | | -3y+15=15 | | y+1=-3(x-2) | | -2x-1=-2x+1 | | 4x+(x+6)=-26-3x | | 5n-1= | | y=-2(0)-1 | | -y/7=-28 | | 4x+(6x-44)=180 | | 4x+(x+6)=3x-(-26) | | 16(2x-8)=4(8x+5) | | 2p+14=89 | | z+16=-4 | | X+(20+x)=180 | | 2.7(14q+7.2)-3q=9 | | 4(t-3)+8t=6(2t+2)-9 | | 5p=65 | | (X+20)=x | | 14r^3-23r^2+8r=0 | | 30-10n=20 | | -20+10n=40 | | 4e^2x-3=2 | | -10-2n=20 | | 2t+11t=114 | | 4+12p-2=8p+74-4p | | 2+3p=12+2p | | y=2y-2 | | .9w-.6w+.2w=2 |